Studi Komparatif Penggunaan Platform Zoom dan Google Classroom sebagai Media Perkuliahan Daring - Intan Cynara Valentina Putri; Rahmi Mudia Alti; Yoana Nurul Asri; Ike Yuni Wulandari (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2023)
In this study, a comparative study was conducted on the use of the Google Classroom and Zoom Meeting platforms during online lectures held at Nurtanio University. The object of research is students from various study programs at Nurtanio University, totaling 82 people. Data were obtained from questionnaires filled out by students on a google form with an ordinal scale. The questionnaire is divided into three components (lecture implementation, lecturer capabilities, and facilities and infrastructure) with a total of 15 statement items that compare perceptions of using Google Classroom and Zoom platforms. Overall, students gave a perception of the